Shell and Double Concentric Tube Heat Exchanger Calculations and Analysis (Journal of Engineering, 2015)
This study concerns a new type of heat exchangers, which is that of shell-and-double concentric tube heat exchangers. The case studies include both design calculations and performance calculations.       The new heat exchanger design was conducted according to Kern method. The volumetric flow rates were 3.6 m3/h and 7.63 m3/h for the hot oil and water respectively. The experimental parameters studied were: temperature, flow rate of hot oil, flow rate of cold water and pressure drop.A comparison was made for the theoretical and experimental results and it was found that the percentage error for the hot oil outlet temperature was (- 1.6%). The percentage errors for the pressure drop in the shell and in the concentric tubes were (17.2%) and (- 39%) respectively. For cold water outlet temperature, the percentage error was (- 3.3%), while it was (18%) considering the pressure drop in the annulus formed. The percentage error for the total power consumed was (-10.8%).A theoretical comparison was made between the new design and the conventional heat exchanger from the point of view of, length, mass, pressure drop and total power consumed.